dsHaE93 shows a high potential for the pest control of Helicoverpa armigera by inhibiting larval-pupal metamorphosis and development of wing and ovary - Kai Wang; Longlong Sun; Mengdan Zhang; Shuting Chen; Guiying Xie; Shiheng An; Wenbo Chen; Xincheng Zhao (Journal of Integrative Agriculture)
The ecdysone-induced transcription factor E93 in model insects plays multiple roles in the insect metamorphosis processes, such as remodeling larval tissues and determining adult tissue formation. The knockdown of E93 in insects leads to incomplete metamorphosis, suggesting that E93 is a potential target for pest control. In this study, the HaE93 gene in the cotton bollworm Helicoverpa armigera, a polyphagous pest of various commercial crops worldwide, was identified and found to have high expression in the egg, prepupal, and pupal stages. The injection of dsHaE93 induced about 60% mortality in H. armigera at the larval-pupal stage. About 30% survived but showed delayed pupation and abnormal wings, and the females developed reduced ovaries. Therefore, about 90% of the HaE93 knockdown individuals failed to reproduce before they died. The results of qRT-PCR showed that the expression levels of ecdysone primary-response genes, chitin synthesis-related genes, and wing and ovary development-related genes were reduced in HaE93 knockdown H. armigera. These results indicated that HaE93 plays a critical role in larva-pupa-adult metamorphosis and the development of the cuticle, wing, and ovary in female H. armigera by regulating the expression of the associated genes. Bioassays of dsHaE93 administered by either oral delivery or injection showed similar knockdown results, which suggested that HaE93 can be used as a target gene for the RNAi control of the pest H. armigera.